The impact of extreme weather condition on the voltage regulation in distribution systems with high penetration of roof-top photovoltaic - Weiqi Pan (Elsevier, 2021)
With the rapid growing penetration of solar power, extreme weather conditions may cause disturbance to power grids. Previous works have studied the impact of extreme weather conditions on active power balance at transmission level, while few studies investigated the potential voltage issue in distribution systems. As most small-scale rooftop photovoltaics are invisible to system operators and cannot participate in voltage regulation in practice, the sudden increase of the unknown amount of reactive power demand caused by extreme weather conditions may lead to a severe voltage fluctuation in the distribution systems with high penetration of rooftop photovoltaics. Hence, this paper investigates this potential voltage issue. We first explicitly modelled the solar power output during extreme weather conditions, and demonstrated the voltage issue in IEEE 33-bus system. Then, we formulated a model for optimal deployment of smart inverters to empower the rooftop photovoltaics at selected nodes to mitigate the voltage issue with minimum cost. With the optimal and efficient allocation plan generated by the proposed model, the distribution systems, with high penetration of solar power, are expected to remain stable and robust to extreme weather conditions.